Towards an Implementation of the Concepts of E-Learning 2.5 Through one Group of Ten Masterâ??s Learners: Case of the UML Course - Sbihi, Boubker; El Kadiri, Kamal Eddine; Aknin, Noura (International Journal of Emerging Technologies in Learning (iJET), 2013)
The aim of our article is to apply the concepts of the E-learning 2.5 in a group of ten Masterâ??s students during the UML course in the I-School of Rabat, Morocco. This survey generated interesting results on the collaborative approach during the UML course. Indeed, 50% of the students find the learning method very satisfactory and 40% satisfactory. Learners are also satisfied with the content published on the class wiki since 50% is very satisfied and 30% is satisfied. This very promising and flexible approach in time and cost can complete or replace traditional learning of a small group of learners. It adds the possibilities of self-evaluation compared to the E-learning 2.0 opportunities and therefore proposes a simple, collaborative, constructive and measurable e-learning which covers a wide public composed mainly of the younger generations.